In-service teacher training for portfolio assessment in reading an action-reflection-action research - Cruz, Josephine Morelos (2005)
An In-Service Teacher Training (INSET) on Portfolio Assessment (PA) premised on Lewin's action research spiral model composed of planning, acting, observing and reflecting stages were developed and validated in this study. The instruments used were questionnaire on teachers' knowledge of portfolio assessment using Likert scale, quiz on PA, teachers' and students' reflection sheets, teachers' journals and interview schedules for both teachers and students. Findings showed that prior to the INSET, the teachers had insufficient knowledge on portfolio assessment implementation. They showed apprehension on its implementation in the classroom due to their voluminous work as teachers. Furthermore, results showed that time is one of the vital factors in the action research spiral model.